Kartografske zbirke in konceptualne spremembe v pojmovanju kart in kartografije - Šolar, Renata (Knjižnica, 2016)
Purpose: The article addresses the problem of conceptual changes in the concept of maps and cartography that are reflected in the work in cartographic collections of libraries. The introductory part is followed by a theoretical overview which highlights the development and changes of the definition of the term map. It also emphasizes conceptual changes between the web cartography and geographic information systems (GIS). The article further systemizes characteristics of geospatial data, which differ from others in terms of size, diversity and the rate of change - this requires additional effort in cataloguing, management and preservation. The emphasis is on Geo- Hydra, geospatial data infrastructure of Stanford University library and cartographic collection of the Cartography and Geological Institute of Catalonia with its virtual maps in geospatial infrastructure in Catalonia - both are examples of cartographic collections of academic and special libraries that provide a rapid and easy access to complex geospatial data. Methodology/Approach: The desk review presents modern findings on conceptual changes at the level of real / virtual map and online cartography, and systematized characteristics of geospatial data as well. Content analysis shows efforts required in cataloguing, management and long-term preservation of spatial data in order to enable effective access to geoinformation. Results: Even though geospatial data are generated according to the established standards, results of content analysis show that there are still many unresolved issues in their capture, management and storage. At present, only few map collections are effectively coping with their complex structure. Research limitations: Relevant literature is available mostly for map and geoinformation collections from the US. Resources for European countries are scarce.
Keywords: cartography; geospatial data; kartografija; Kartografske zbirke; Map collections; prostorska podatkovna infrastruktura; prostorski podatki; spatial data infrastructure